Expression of drug resistance proteins in triple-receptor-negative tumors as the basis of individualized therapy of the breast cancer patients - Chekhun, V.F.; Zhylchuk, V.E.; Lukyanova, N.Yu.; Vorontsova, A.L.; Kudryavets, Yu.I. (Experimental Oncology, 2009)
Aim: To evaluate the efficacy ofthe application of various chemotherapy schemes based on the immunohistochemical study of expression
patterns of proteins associated with the drug resistance P-glycoprotein (P-gp), glutathione-S-transferase (GST), metallothioneins
(МТ) of breast cancer (BC) patients with the triple-receptor-negative (RE–, RP–, HER-2/neu–) cancer. Methods and Results: P-gp,
GST and МТ expression in BC-biopsy samples from 60 BC patients was evaluated by immunohistochemical analysis. The results
of the clinical observations showed that 3-years relapse-free survival rate of the patients of with P-gp, GST and МТ-positive tumors
treated with taxoter + adriablastin / taxoter + cyclophosphamide (ТА/ТС), gemcitabine + carboplatin, or TC + bevacizumab was
61.5%, 78.6% and 81.2% respectively, vs 41.2% in the control group with P-gp, GST and МТ-negative tumors treated with adriablastin
+ cyclophosphamide (p < 0.05), while overall survival rates were 84.4%, 92.6% and 93.8% respectively vs 70.6% in the control
group (p < 0.05). Conclusion: The study points on the possibility to elevate the efficiency of polychemotherapy by its individualization
based on the expression patterns of Р-gp, GST and MT on tumor cells of the patients with the triple-receptor-negative BC.